Identification of a Sgo2-Dependent but Mad2-Independent Pathway Controlling Anaphase Onset in Fission Yeast - John C. Meadows; Theresa C. Lancaster; Graham J. Buttrick; Alicja M. Sochaj; Liam J. Messin; Maria del Mar Mora-Santos; Kevin G. Hardwick; Jonathan B.A. Millar (Cell Reports, 2017)
The onset of anaphase is triggered by activation of the anaphase-promoting complex/cyclosome (APC/C) following silencing of the spindle assembly checkpoint (SAC). APC/C triggers ubiquitination of Securin and Cyclin B, which leads to loss of sister chromatid cohesion and inactivation of Cyclin B/Cdk1, respectively. This promotes relocalization of Aurora B kinase and other components of the chromosome passenger complex (CPC) from centromeres to the spindle midzone. In fission yeast, this is mediated by Clp1 phosphatase-dependent interaction of CPC with Klp9/MKLP2 (kinesin-6). When this interaction is disrupted, kinetochores bi-orient normally, but APC/C activation is delayed via a mechanism that requires Sgo2 and some (Bub1, Mph1/Mps1, and Mad3), but not all (Mad1 and Mad2), components of the SAC and the first, but not second, lysine, glutamic acid, glutamine (KEN) box in Mad3. These data indicate that interaction of CPC with Klp9 terminates a Sgo2-dependent, but Mad2-independent, APC/C-inhibitory pathway that is distinct from the canonical SAC.